Espaçamento entre fileiras e densidade de plantio em dois cultivares de arroz, sob irrigação por aspersão - Bezerra de Oliveira, Aldo; Starling Brandão, S; R Condé, Alcides; M del Giudice, Renato (Revista Ceres, 2025)
The effect of three row with — 30, 50 and 70 cm — and three plant densities — 58, 116 and 174 plants/m2 — on grain production, principal yield components and other agronomic characteristics of the rice varieties ‘I1.A.C. 1246’ and were studied ‘Batatais’, grown under sprinkle irrigation were studied in trials near Viçosa, Minas Gerais, Brazil.